Yoga for the rest of us. Heart healthy yoga [videorecording (DVD)]. - Cappy, Peggy (WGBH, 2009)
Viewers who make this their daily yoga routine will improve their heart health as well as their overall health. The workout centers around sun salutations that work the entire body. Features dynamic movements for the spine, lunges, side stretches, breathing techniques, leg stretches, and relaxation poses. Includes a five-minute breathing technique that, once learned, can be done anywhere.